New Insights on the Regulatory Gene Network Disturbed in Central Areolar Choroidal Dystrophy—Beyond Classical Gene Candidates - Kazmierczak de Camargo, João Paulo; Prezia, Giovanna Nazaré de Barros; Shiokawa, Naoye; Sato, Mario Teruo; Rosati, Roberto; Beate Winter Boldt, Angelica (Frontiers in Genetics, 2022)
Central areolar choroidal dystrophy (CACD) is a rare hereditary disease that mainly affects the macula, resulting in progressive and usually profound visual loss. Being part of congenital retinal dystrophies, it may have an autosomal dominant or recessive inheritance and, until now, has no effective treatment. Given the shortage of genotypic information about the disease, this work systematically reviews the literature for CACD-causing genes. Three independent researchers selected 33 articles after carefully searching and filtering the Scielo, Pubmed, Lilacs, Web of Science, Scopus, and Embase databases. Mutations of six genes (PRPH2, GUCA1A, GUCY2D, CDHR1, ABCA4, and TTLL5) are implicated in the monogenic dominant inheritance of CACD. They are functionally related to photoreceptors (either in the phototransduction process, as in the case of GUCY2D, or the recovery of retinal photodegradation in photoreceptors for GUCA1A, or the formation and maintenance of specific structures within photoreceptors for PRPH2). The identified genetic variants do not explain all observed clinical features, calling for further whole-genome and functional studies for this disease. A network analysis with the CACD-related genes identified in the systematic review resulted in the identification of another 20 genes that may influence CACD onset and symptoms. Furthermore, an enrichment analysis allowed the identification of 13 transcription factors and 4 long noncoding RNAs interacting with the products of the previously mentioned genes. If mutated or dysregulated, they may be directly involved in CACD development and related disorders. More than half of the genes identified by bioinformatic tools do not appear in commercial gene panels; calling for more studies about their role in the maintenance of the retina and phototransduction process, as well as for a timely update of these gene panels.